The Anthropological Turn: Cultural Practices for the Development of Human Complexity - Alexander G. Asmolov; Pavel D. Rabinovich; Kirill E. Zavedensky (National Research Mordova State University, 2023)
Introduction. In the worldwide situation of collision accompanied with systemic crises, it is proposed to raise a reflexive question - how institutions and knowledge-systems can be arranged to support complexity, diversity, and subjectivity of Human action. Authors propose an approach to overcoming systemic gaps through reframing and re-actualization of the field of socio-humanitarian practices. It is necessary to "build up" the environment of integration of sciences and cultural practices of human development. The article presents the key provisions of the "Anthropological Turn" approach, provides an overview of the foundations and basic ideas, as well as specific practical models of activity. Materials and Methods. The "Anthropological Turn" sets a fundamentally different framework and actually highlights the objects and mechanisms of interpretation of the results for future humanitarian research. "Anthropological Turn" research program overcomes the naturalistic approach in the study of humanitarian processes. Results. Authors propose and describe four basic practical and organizational models. These models are acting as the activity infrastructure for the implementation of the ideas of the Anthropological Turn: the historical and evolutionary methodology for designing universities of the future; productive activities for the socio-cultural development of territories and technological entrepreneurship in childrenʼs and adult communities; search, development and replication of humanitarian (cultural, educational, etc.) practices; the family as an institution for the development of subjectivity and human identity. Discussion and Conclusion. The described approaches and implemented projects made an ecosystem of educational solutions. On the one hand, they provide support for the development of the professional and educational space and innovative activities of the subjects of Russia, the creation and dissemination of promising educational practices, training of high-level professionals for the social sphere, business; and, on the other hand, it contributes to the formation of a dynamic system for the implementation of continuous professional development of personnel.